Learning Medium for Students with Visual Impairment - et. al., R.Vaijayanthi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Students with Visual impairment benefit from building a strong foundation of literacy skills during their preschool years, a goal that is often more challenging for young Braille readers who lack access to the incidental learning readily absorbed by typically sighted children. Braille remains the main medium of communication for persons who are blind. The Disability Act of 2003, USA on its part stipulated that Learning Institutions should take into account the special needs for persons with disabilities with respect to the entry requirements, pass marks, curriculum, examinations, auxiliary services, use of school facilities, class schedules and other similar considerations. The Act also emphasized that provisions should be made in all parts of the country for an integrated system of special and non formal education for persons with all forms of disabilities. It also proposed for the establishment where possible of Braille and recorded libraries for persons with visual impairments. Keeping these points in view an attempt was done to know the Braille literacy medium for students with visual impairment. The objectives of the study were to examine the learning medium of students with visual impairment in Inclusive and Special schools and to find out the appropriate educational devices used by visually impaired students .Survey method was used to gather the details. The study was carried out with Ninety four students with visual impairment and thirty five special teachers. Qualitative analysis was done to analyze the learning medium for students with visual impairment. Results revealed that majority of the samples(77.66%) were students with Low vision than totally blind students(22.34% . The study revealed that students with visual impairment use book print ,print& audio ,reader service, digital/recorded books , audio tapes/speech input, large print with/without the aid of magnifiers as their learning medium. Nearly 52.38% of21 totally visually impaired students used Braille as learning medium.